Fossil imprints from oceans of the past - Henderiks, Jorijntje (Science (American Association for the Advancement of Science), 2022)
Marine phytoplankton show notable resilience during extreme ocean states Throughout the long opera of Earth’s oceans, algal blooms have dotted across the seascape like a cacophony of pop-up solos. Phytoplankton—the microalgae at the bottom of marine food webs—compete with each other for sunlight and nutrients to sustain photosynthesis and turn inorganic carbon into organic matter. The occasional blooms of these microalgae, often at scales visible from space, are followed by a chain of life and decay, as different species begin and end their life cycles, following each other in close succession. Phytoplankton play a pivotal role in global biogeochemical cycles and feedbacks on climate and ocean chemistry. On page 853 of this issue, Slater et al. ( 1 ) provide evidence that coccolithophores, a group of calcifying haptophyte algae, remained prominent producers throughout prolonged periods of ocean warming and oxygen depletion in the past, challenging the assumption ( 2 ) that they had suffered “calcification crises” under previous extreme ocean conditions.